Evaluacija prognostičkih markera srčane insuficijencije pacijenata tretiranih perkutanom koronarnom intervencijom nakon akutnog infarkta miokarda - Marjanović, Dajana; Miljković, Jelena; Stanetić, Bojan (Scripta Medica, 2022)
Background / Aim: The concentration of N-terminal brain natrium peptides (NT-proBNP) is an important marker within the diagnostic and prognostic analysis of patients with chronic heart failure. In patients with ST-segment elevation myocardial infarction, natriuretic peptides are dominant predictors of death, heart failure and additional myocardial infarctions. The aim of this study was to correlate prognostic markers of heart failure following acute myocardial infarction. Methods: 193 patients with myocardial infarction were divided into two groups: 69 patients with NT-proBNP ≤ 1000 pg/mL and 124 patients with NT-proBNP > 1000 pg/mL. During the hospitalisation, laboratory data, clinical data and information on previous medications were collected. Echocardiography was used to identify left ventricular ejection fraction (LVEF). All statistical analysis were done in SPSS, version 23. Results: The group with elevated NT-proBNP (> 1000 pg/mL) was older (p < 0.001) and suffered more often of arterial hypertension (p = 0.04) and atrial fibrillation (p = 0.003). Heart rate was higher and LVEF was lower in patients with elevated NT-proBNP values (p < 0.001). Mean LVEF in the 193 patients was 46.86 %. In both linear and binary logistic regression analysis multiple predictors of elevated NT-proBNP have been identified. Conclusion: Increased ranges of NT-proBNP in patients following acute myocardial infarction are in correlation with decreased LVEF, elevated high-sensitive troponin I, lactate dehydrogenase, urea, creatinine, C-reactive peptides. This may guide clinicians to assess and treat early stages of heart failure.